Chemical Composition Analysis for Source Identification of PM2.5 in Muang District of Ubon Ratchathani Province - Salao, Supannika; Potatong, Natapol; Kammoongkun, Priyaporn; Choomanee, Parkpoom (Burapha Science Journal, 2026)
This research aimed to analyze the concentration and the distribution of organic carbon and element carbon of particulate matter with an aerodynamic diameter less than 2.5 micrometers (PM2.5) in the ambient air of Muang District, Ubon Ratchathani Province. The air samplings were carried out at Ubon Ratchathani Rajabhat University and Thung Sri Mueang (public park) in dry season during 18 February to 17 April 2019. Mass concentration data were collected for 24 hours (from 6:00 am.to 6:00 am.of the next day) using the Mini Volume Air Sampler, with Minivol TAS model. The Thermal/Optical Transmittance (TOT) method following the NIOSH870 protocol was used to determine the amounts of organic carbon (OC) and element carbon (EC). The concentrations of PM2.5 at Ubon Ratchathani Rajabhat University and Thung Sri Mueang were in the ranges of 0.037 – 0.061 mg/m3 and 0.001 – 0.028 mg/m3, respectively. From the study of carbon compound in PM2.5 samples, it is found that OC concentrations were higher than EC concentrations in both areas. The concentrations of ion compositions in ambient PM2.5 were found predominant species as SO42-, NO3- and NH4+. The distribution of eight carbon fractions (OC3, OC2, OC4, OC1, PC, EC1, EC2 and EC1) were determined and the OC/EC ratios were in the range of 4.441 – 9.655. The results suggested that biomass burning and motor vehicle exhaust significantly contributed to the carbonaceous particles in Muang District, Ubon Ratchathani Province.